2000
DOI: 10.1161/01.hyp.36.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Role of Tumor Necrosis Factor-α Gene Locus in Obesity and Obesity-Associated Hypertension in French Canadians

Abstract: Abstract-Obesity represents a serious risk factor for the development of cardiovascular diseases, including hypertension.Segregation studies suggest that obesity and obesity-associated hypertension may share some genetic determinants. The results of the present candidate gene investigation suggest that in hypertensive pedigrees of French-Canadian origin, one such determinant is the tumor necrosis factor (TNF)-␣ gene locus. Gender-pooled quantitative sib-pair analysis demonstrated a significant effect of the ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 35 publications
3
57
0
3
Order By: Relevance
“…For example, TNF-α and IL1-β decrease the production and expression of leptin, an anorexigenic hormone formed in the adipose tissue [32]. Polymorphisms of the genes encoding TNF-α receptor have been associated with leptin-resistance and obesity [33,34]. In studies of rodents, injection of TNF-α and IL-1 initially reduces food intake.…”
Section: Discussionmentioning
confidence: 99%
“…For example, TNF-α and IL1-β decrease the production and expression of leptin, an anorexigenic hormone formed in the adipose tissue [32]. Polymorphisms of the genes encoding TNF-α receptor have been associated with leptin-resistance and obesity [33,34]. In studies of rodents, injection of TNF-α and IL-1 initially reduces food intake.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, gene polymorphisms of TNF have been associated with obesity by many investigators. [24][25][26][27][28][29][30][31] Infiltrative macrophages have been shown to be increased and to be the main source of TNF-a expression in adipose tissue in obese mice. 32,33 MIF could upregulate TNF-a secretion by macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…13 By contrast, only a few of these studies give sufficient attention to phenotypes reflecting central obesity (eg abdominal visceral fat, WHR, waist circumference, sagittal abdominal diameter). Table 1 54,55 peroxisome proliferative activated receptor g, coactivator 1 (PPARGC1), 56 tumor necrosis factor (TNF), 57,58 tumor necrosis factor receptor superfamily, member 1B (TNFRSF1B), 59 uncoupling protein 2 (UCP2), 60 and uncoupling protein 3 (UCP3). 61 In addition to the positive association studies summarized in Table 1, the number of 'negative' reports, which are only partly reviewed below, is also increasing very rapidly.…”
Section: Association Studies In the Literaturementioning
confidence: 99%
“…104,105 Some, but not all studies, have indicated a key role for the À308 variant of the TNF gene in the pathogenesis of obesity and obesity-associated insulin resistance. [57][58][59][106][107][108][109][110][111] However, only four of these studies include anthropometric indices of central obesity. 57,58,110,111 Among these studies, two reported associations between the GÀ308A variant of the TNF and measurements of central obesity.…”
Section: Tumor Necrosis Factor Gene (Tnf)mentioning
confidence: 99%
See 1 more Smart Citation